2022
DOI: 10.3389/fonc.2022.846044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Platelet-Large Cell Ratio In Myelodysplastic Syndromes

Abstract: BackgroundMyelodysplastic syndromes (MDSs) are a very heterogeneous group of myeloid disorders with high prevalence and risk of developing acute myeloid leukemia. The more accurate risk stratification can provide a better guidance of treatment. The platelet–large cell ratio (P-LCR) is a parameter reported in complete blood cell count tests, and was associated with many diseases, but its role in MDS is not clear.PurposeThis study aims to explore the impact of the P-LCR on the prognosis of patients with MDS, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…[20] Also in another study, it is shown that P-LCR can be used as a prognostic parameter in myelodysplastic syndromes (MDS) patients as survival time was shorter especially in patients with low P-LCR. [21] Based on our results, we suggest that P-LCR may prove to be as useful as already established hematologic parameters in patients with a risk of cytokine storm, with the additional advantages of being an inexpensive and practical potential prognostic parameter.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…[20] Also in another study, it is shown that P-LCR can be used as a prognostic parameter in myelodysplastic syndromes (MDS) patients as survival time was shorter especially in patients with low P-LCR. [21] Based on our results, we suggest that P-LCR may prove to be as useful as already established hematologic parameters in patients with a risk of cytokine storm, with the additional advantages of being an inexpensive and practical potential prognostic parameter.…”
Section: Discussionmentioning
confidence: 62%
“…Also in another study, it is shown that P-LCR can be used as a prognostic parameter in myelodysplastic syndromes (MDS) patients as survival time was shorter especially in patients with low P-LCR. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…We reported significantly higher postpartum P LCR in treated thrombophilia patients than in normal patients. Generally, the platelet‐large cell ratio (P‐LCR) increased with age, 38 but in the case of postpartum patients, a higher value of P LCR can be interpreted as the presence of a high percentage of new platelets characterized by a greater size, 39 since young platelets are larger and more active than mature cells, 40 and contain greater amounts of thromboxane A1 and beta‐thromboglobulin 41,42 . This means that labor triggered the release of more numerous young platelets and an increase in P‐LCR, but only in thrombophilia patients.…”
Section: Discussionmentioning
confidence: 99%
“…In link with this observation, Chen et al recently identified the platelet-large ratio (P-LCR), the percentage of platelets larger than 12 fL, as a prognostic factor in MDS in uni- and multivariate analyses. A low P-LCR fraction was associated with a decreased overall survival in a cohort of 122 MDS patients [ 20 ]. Ravalet et al identified PDW on the DxH 800 as a parameter predictive of MDSs [ 12 ].…”
Section: Cell Population Datamentioning
confidence: 99%